Analisis Komunikasi Politik dalam Kampanye Pemilu: Pendekatan Kualitatif terhadap Strategi dan Dampaknya di Media Sosial - Ardiansyah, Fiki; Muhaimin (As-Syirkah: Islamic Economic & Financial Journal, 2024)
This study aims to analyze political communication in election campaigns using a qualitative approach, focusing on the strategies employed and their impact on social media. In the context of the growing use of social media as a primary platform for political campaigns, this research examines how politicians and campaign teams utilize social media to convey political messages, build images, and influence public opinion. Data were collected through in-depth interviews with political campaign practitioners and content analysis from various social media platforms. The findings indicate that effective communication strategies on social media involve engaging content, active interaction with the audience, and message adaptation according to the platform's characteristics. Additionally, the impact of these strategies is observed in increased political participation, changes in public perception, and voter mobilization. These findings provide valuable insights for political practitioners and communication researchers regarding the dynamics of political communication in the digital era.